13 Can the 'death cafÉ' concept be adapted for use in healthcare professional learning and development?. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Howorth, Kate; Thomson, Richard; Paes, Paul
Abstract : Background: Much deep learning is about thinking, talking, reflecting and shaping ideas through interactions with others. 'Death cafes' are examples of modified 'World Café' methods designed to create an informal, relaxed atmosphere where conversation allows people to recognise their own personal values, share knowledge and understand the world around them. This project was created to determine if this could be applied to healthcare professional development. Methods: Two 'death cafes' were run, one with a Palliative Care team and one a group of hospital-based doctors. Groups of 3–6 people sat at tables with refreshments and a set of cards with stimulus questions on them related to death and end of life care. There was then informal discussion at the tables with people sharing their experiences and gaining new insights based on the group's response to questions. After the Café participants were invited to complete an evaluation looking at its potential benefits, relevance to their role and suggested improvements. Results: All participants saw benefits of using the Café for their learning. They reported the relaxed atmosphere generated open and interesting conversation and prompted discussion about end of life. The majority felt more confident in discussing death with patients and their families afterwards, including 77% of the Palliative Care team. Many reported they could use this format in their roles for wider team training sessions, medical student teaching or with certain patient groups. Conclusions: Death cafes proved to be an effective tool for staff development and increased healthcare professionals' confidence in discussing death. We will now expand this through using a similar format as an educational tool with medical students. The sessions will focus on training in end of life care; the process will be evaluated in terms of design and learning gain. The results will be available for the conference.